Galician Writers, Galician Literature in Madrid: Literary Circle at Café Lyon d’Or (1952-1954) - Alonso Montero, Xesús (Madrygal. Revista de Estudios Gallegos, 2004)
This article describes the first Galician literary (and also slightly political) circle during the postwar period in Madrid. Its author, a student in those days, was the most active component of the group of youngsters. The study is completed by an appendix consisting of several texts, some of them unpublished, including words from Anxel Rodríguez, who used to enthusiastically attend the gatherings held at the café Lyon d’Or at that time. Galician writers, group of youngters, Café Lyon D’Or, Galician literature in Madrid.